Navigating the Classroom: Reflections on Teaching Practice - Naseem, Afshan Naseem (PJE, 2024)
The teaching practicum aims to address the transition of prospective teachers by providing them with an opportunity to apply their learning in a practical setting. The objective of this study is to investigate the experiences of prospective teachers during their teaching practicum. The sample for this qualitative research consisted of 16 prospective teachers in their final year of the program. Data collection was done through semi-structured interviews, where participants reflected on their experiences. The collected data was then transcribed. The validity of the interview instrument was ensured by experts in the field. The semi-structured interview questionnaire comprised of thirteen questions, focusing on six factors. The interview data was manually analyzed using thematic content analysis. Prospective teachers encountered challenges while working with individuals who displayed irritating, arrogant, inflexible, uncooperative, and rude behavior. The research findings also highlight the significance of lesson planning, effective classroom management, and assessment strategies. Additionally, the results shed light on the strengths and weaknesses of the participants. The study recommends that researchers engage in discussions about teaching practicum prior to its commencement, in order to enhance understanding and preparation.